Analisis Studi Kelayakan Bisnis Butik Baju Muslimah Sha&Sa - Azzahra, Nabila; Ramadhani, Nabila Rizki; Lubis, Nazia Safira; Lubis, Putri Kemala Dewi (Peneliti.net, 2025)
This research aims to evaluate the business feasibility of the Muslimah clothing boutique